THE CONCEPT OF APPLICATION OF MACHINE LEARNING IN THE ENVIRONMENT INTERNET OF THINGS - Sulindawaty Sulindawaty; Jijon R Sagala; Penda Sudarto Hasugian (INFOKUM, 2021)
Machine Learning is an application of computers and mathematical algorithms adopted by means of learning that comes from data and produces predictions in the future. The learning process in question is an attempt to acquire intelligence through two stages, including training and testing. The Internet of Things is a network that can connect anything in the supply chain, including people, machines and systems, where efficient supply chain management is guaranteed. This is done through visualizing any object/thing in the supply chain by monitoring, tracking and providing a third dimension to organizational data, that if analyzed can improve all supply chain processes. In the IoT environment, Machine Learning is very suitable to be applied which can provide many benefits including Resolving Data Inefficiency Problems, Automating Business Processes, Visualizing Supply Chain Management (Supply Chain), Risk Management and Maximizing Profits. By implementing IoT and Machine Learning, of course, it can fulfill business opportunities, namely: process optimization, speed optimization, adaptability optimization and reliability optimization